An assessment of perceived prioritisation and resource allocation for health policy and systems research in West Africa - Chigozie J Uneke (Sax Institute, 2021)
Objectives: Globally, adequate funding is a strong underpinning to advance health policy and systems research (HPSR) and ensure its impact on strengthening health systems. This study examined the perceived prioritisation, and resource allocation for HPSR in West Africa. Methods: A desk review was conducted of literature related to HPSR funding published between January 2010 and December 2019, sourced from various databases and government websites. This was followed by in-depth interviews with senior decision makers and HPSR and non-HPSR research leaders (n = 33) across nine West African countries: Benin, Burkina Faso, Côte d’Ivoire, Gambia, Ghana, Liberia, Nigeria, Senegal and Sierra Leone. Results: The majority of the study participants were from ministries of health in their countries (66.7%). All countries except Sierra Leone had a program dedicated to health policy research and/or health planning/program research. There was no specific funding for health research nor HPSR in most countries and a mixed model (demand and supply led) was employed in most instances. HPSR was only considered a priority in two of the nine countries and specific funding for it was non-existent in all nine countries. In all countries, donor agencies played predominant roles in setting health research priorities and resource allocation decisions. Infectious disease and maternal/child health research were the research categories with the highest level of funding. There was limited capacity for HPSR, with a pronounced gap between researchers and policy makers. Stakeholder advocacy, basket funding for health research, multi-stakeholder institutional and individual HPSR capacity building were the major recommendations for improving the status and funding of HPSR. Conclusions: This study showed that both health research and HPSR were considered low priorities, with no designated funding (budget line) and inadequacy of funding disbursement in the surveyed countries in West Africa. Health research was largely conducted as prioritised and funded by the donor agencies. Given donor fatigue and the transitioning of donor funding, and the pivotal role of HPSR in strengthening health systems, there is an urgent need for West African states to commit to prioritising and funding HPSR and HPSR capacity development.